(untitled) (Costos y Gestión, 2025)
The main objective of this research is to evaluate the export capacity of a Small and Medium-sized Enterprise that engages in the secondary activity of producing sunflower oil. The methodology corresponds to a case study, in which a specific phenomenon was analysed in depth regarding the chosen unit of analysis. The data collection techniques applied were: documentary and content analysis, implemented through spreadsheets; observations, structured and unstructured interviews. To analyse the economic and financial feasibility of the project, the starting point was the calculation of the selling price. The calculated FOB price would be competitive, and the Net Present Value is positive for the base scenario. Currently, the company does not have export capacity due to the following reasons: it lacks a strong presence in the domestic market, does not have export and marketing departments within its structure, and lacks the necessary formalization of its processes and procedures. If these factors were addressed, the company meets the remaining conditions to export: a strong organizational structure, standardized processes and procedures, an export-oriented mindset from its founders, and economic and productive efficiency.